2011
DOI: 10.1007/s00204-011-0721-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of the γH2AX assay for assessing the genotoxicity of bisphenol A and bisphenol F in human cell lines

Abstract: Bisphenol A (BPA) and bisphenol F (BPF) are widely used to manufacture plastics and epoxy resins. Both compounds have been shown to be present in the environment and are food contaminants, with, as a result, a low but chronic exposure of humans. However, the fate and possible bioactivation of these compounds at the level of human cell lines was not completely elucidated yet. In this study, we investigated the ability of human cells (intestinal cell line: LS174T, hepatoma cell line: HepG2, and renal cell line: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 51 publications
3
110
0
Order By: Relevance
“…However, structural differences alone cannot clearly explain the structure-activity relationship in this series of BPA analogues or why BPF, BPAF, BPZ, and DMBPA did not induce DNA damage, and why BPA and BPS did induce signifi cant DNA damage only after 24 h of exposure. It has recently been demonstrated that BPA and BPF are metabolised in HepG2 cells predominantly to conjugated sulphate metabolites (31,60). However, we still do not know to what extent BPA and its analogues are biotransformed into reactive quinone intermediates in HepG2 cells, and how stable these intermediates are.…”
Section: Bisphenol-induced Dna Strand Breaks In Hepg2 Cellsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, structural differences alone cannot clearly explain the structure-activity relationship in this series of BPA analogues or why BPF, BPAF, BPZ, and DMBPA did not induce DNA damage, and why BPA and BPS did induce signifi cant DNA damage only after 24 h of exposure. It has recently been demonstrated that BPA and BPF are metabolised in HepG2 cells predominantly to conjugated sulphate metabolites (31,60). However, we still do not know to what extent BPA and its analogues are biotransformed into reactive quinone intermediates in HepG2 cells, and how stable these intermediates are.…”
Section: Bisphenol-induced Dna Strand Breaks In Hepg2 Cellsmentioning
confidence: 97%
“…In their recent study, Audebert et al (31) reported that 24-hour exposure to BPA (50 μmol L -1 and 100 μmol L -1 ) and BPF (100 μmol L -1 ) reduced the viability of several cell lines, including HepG2 cells. However, they determined cell viability by measuring DNA content with in-cell western (ICW) assays, while we used an MTT assay that is based on the measurement of the metabolic activity of living cells.…”
Section: Bisphenol Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, DSB can also help to kill cancer cells 153. Thus, this method is used in different fields ranging from cancer chemo‐ and radiotherapy154 or drug discovery155 to in vitro toxicology testing of environmental pollutants 150…”
Section: The γH2ax Assaymentioning
confidence: 99%
“…In rat brain tissue, PFOS activates calcium signalling and c-Fos, as well as c-Jun (32) Liu et al (2010a, b) This study applied a genotoxicity assay based on the detection of histone H2AX phosphorylation to compare bisphenol A and bisphenol F. Bisphenol A was not found to be genotoxic, whereas bisphenol F showed positive effects (33) Audebert et al (2011) Sodium fluoride suppresses proliferation and induces apoptosis in cultivated osteoblasts. This effect was caused by decreased insulin-like growth factor-1 expression…”
mentioning
confidence: 99%